Development and quality assessment of nutrient-rich cereal-based porridge flour in the Northern Region of Ghana - Agyiri, Martha (2016)
A thesis submitted to The School of Research and Graduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the award of Master of Philosophy(Mphil. Postharvest Technology) Degree.